Factors Affecting Gross Enrollment Rates in Higher Education in Indonesia - Nurjanah, Siti (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
A statistical indicator that expresses educational achievement in a nation as a percentage is the gross enrollment rate. The number of people enrolled in postsecondary education, regardless of age, is compared to the number of individuals between the ages of 19 and 23 in GER HE. Finding the impact of the units under analysis—the Economic Gini Ratio, the Ratio of Lecturers, and the Ratio of the Number of Universities—on the GER of HEs in Indonesia between 2020 and 2022 is the main goal of the research.  A quantitative approach using secondary data is the research methodology employed. A saturated sample from the total population of 102 samples was used. Regression analysis of data panels is the method of data analysis. The cumulative time series data from three years, specifically 2020–2022, make up the data panel that is used. Next, data from several objects (cross section) is utilized, namely data from 34 Indonesian provinces. The study's findings, which were derived using the Fixed Effect Model (FEM), indicate that, for higher education institutions, the economic Gini ratio has a substantial negative impact on GER by -2.038873 between 2020 and 2022. Meanwhile, the ratio of universities to teachers and the ratio of lecturers to universities has no discernible impact on the GER of HEIs in Indonesia between 2020 and 2022.